Non-invasive markers of liver fibrosis and outcome in large vessel occlusion stroke. (August 2021) - Fandler-Höfler, Simon; Stauber, Rudolf E.; Kneihsl, Markus; Wünsch, Gerit; Haidegger, Melanie; Poltrum, Birgit; Pichler, Alexander; Deutschmann, Hannes; Enzinger, Christian; Fickert, Peter; Gattringer, Thomas
Background: Liver fibrosis has been identified as an outcome predictor in cardiovascular disease and has been associated with hematoma expansion and mortality in patients with primary intracerebral hemorrhage. We aimed to explore whether clinically inapparent liver fibrosis is related to neurological outcome, mortality, and intracranial hemorrhage risk in ischemic stroke patients after mechanical thrombectomy. Methods: We included consecutive patients with anterior circulation large vessel occlusion stroke treated at our center with mechanical thrombectomy between January 2011 and April 2019. Clinical data had been collected prospectively; laboratory data were extracted from our electronic hospital information system. We calculated the Fibrosis-4 index (FIB-4), an established non-invasive liver fibrosis test. The main outcomes were postinterventional intracranial hemorrhage, unfavorable functional status (modified Rankin scale scores of 3–6), and mortality three months post-stroke. Results: In the 460 patients (mean age 69 years, 49.3% female) analyzed, FIB-4 indicated advanced liver fibrosis in 22.6%. Positive FIB-4 was associated with unfavorable neurological outcomes and mortality three months post-stroke, even after correction for co-factors [Odds Ratio (OR) 2.15 for unfavorable outcome in patients with positive FIB-4, 95% confidence interval (CI) 1.21–3.83, p  = 0.009, and 2.16 for mortality, 95% CI 1.16–4.03, p  = 0.01]. However, FIB-4 was neither related to hemorrhagic transformation nor symptomatic intracranial hemorrhage. Moreover, atrial fibrillation was more frequent in patients with liver fibrosis ( p  < 0.001). Two further commonly-used liver fibrosis indices (Forns index and the Easy Liver Fibrosis Test) yielded comparable results regarding outcome and atrial fibrillation. Conclusions: Clinically inapparent liver fibrosis (based on simple clinical and laboratory parameters) represents an independent risk factor for unfavorable outcomes, including mortality, at three months after stroke thrombectomy. Elevated liver fibrosis indices warrant further hepatological work-up and thorough screening for atrial fibrillation in stroke patients.